2003
DOI: 10.1007/bf03018364
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Le remplissage vasculaire avec de l’HEA 130/0,4 peut réduire la réaction inflammatoire chez des patients en chirurgie abdominale majeure

Abstract: P Pu ur rp po os se e: : To investigate the effects of intravascular volume replacement therapy on the inflammatory response during major surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 25 publications
3
52
2
6
Order By: Relevance
“…Ap ure experimental haemorrhage may not comparet ot he circumstances of the present study.V olume deficit after cardiac surgery is due to CPB related profound alterations in vascular endothelial barrier,rewarming induced vasodilatation, and fluid loss via chest tube drainage (24). Infusing HES to our patients may have affected the results because of the capacity of HES to blunt the CPB-induced inflammatory process and endothelial activation (25)(26)(27). In addition, the concentration of HA was also lower (4% versus 5%) in our study.…”
Section: Discussionmentioning
confidence: 62%
“…Ap ure experimental haemorrhage may not comparet ot he circumstances of the present study.V olume deficit after cardiac surgery is due to CPB related profound alterations in vascular endothelial barrier,rewarming induced vasodilatation, and fluid loss via chest tube drainage (24). Infusing HES to our patients may have affected the results because of the capacity of HES to blunt the CPB-induced inflammatory process and endothelial activation (25)(26)(27). In addition, the concentration of HA was also lower (4% versus 5%) in our study.…”
Section: Discussionmentioning
confidence: 62%
“…Ringer's lactate solution (RLS) is a frequently used resuscitative fluid, which has been shown to increase serum IL-6, IL-8 [55,56] and TNF-α [56,57] in patients and experimental animals; in addition, RLS can provide lactate as an alternative metabolic fuel [58][59][60][61][62][63][64]. "Lactic acid" was thought to be responsible for tissue damage, and as a consequence, lactate is frequently considered to be a "toxic" compound.…”
Section: The Anti-and Pro-inflammatory Therapies In Apap Toxicitymentioning
confidence: 99%
“…Lowell and co-workers (1990) demonstrated that after major surgery those patients with a body weight increase of over 20% died, but a moderate fluid overload postoperatively could improve the DO 2 (Arkilic et al 2003) as well as the microcirculation in critically ill patients (Lang et al 2003). Nevertheless, many studies report a better physiological outcome using the optimal model of volume replacement (Tølløfsrud et al 1995, Lobo et al 2002, Brandstrup et al 2003, Nisanevich et al 2005).…”
Section: Principles Of Volume Replacement Therapy After Major Surgerymentioning
confidence: 99%
“…Many studies have demonstrated the successful use of HES solutions in maintaining hemodynamic goals after different types of surgery, and in critically ill patients (Boldt et al 1996, Lang et al 2003, Kuitunen et al 2007. HES solutions have a good plasma-expansive property, which lasts several hours.…”
Section: Hemodynamic Effects Of Hydroxyethyl Starchesmentioning
confidence: 99%